Os sujeitos discursivos nas canções de Chico Buarque nos períodos ditatorial e democrático - Barros, Maria Irenilce Rodrigues (2017)
This study analyzes discursive subjects in songs by the Brazilian singer and composer Chico Buarque, based on the historical background of two Brazilian political regimes: the Military Regime, which started in the 1964 Coup d’état and ended in 1984, and the Post-dictatorship/Democratic Regime, which started in 1985 and has been the political system in Brazil until today. We selected eight songs using as a criterion the identification of socially and politically excluded/oppressed subjects, namely street boys, women, and landless workers. The conditions in which discourses were produced, or even their conditions of emergence, had an important character in our discussion, since they register the appearance of discourses as a whole and rebuild discursive occurrences in each space of enunciation. In order to improve corpus analysis and understanding, we considered the following hypothesis: during the Military Regime, Chico Buarque was an artist known for his creative way of composing songs that reproduced very well the social and political anguish, oppression, suffering and misery of subjects in his culture, especially those who suffered from the exclusion conducted by the regime in power; when resurfaced after the Dictatorship Regime, the discursive subject’s positioning in the songs - that is, their discursive voice - seems to have changed, or it may have been (re)directed to another space of discourse that socially and politically integrates this voice in a veiled and/or discreet defense of excluded/oppressed subjects, no longer representing their voices emphatically. Considering this, some questions arose to guide the effect of meanings in our analysis, such as: what was produced in each Brazilian political stratum regarding the ideological position of musical works? Considering the wide dissemination of the author’s name, since this name is attached to the interpreter, the composer, the writer, the screenwriter and others, and also to many discursive genres, why did this artistic expression spread so much inside Brazil and abroad? What is it in the author’s work, or even in the author’s name, that highlights him/it in cultural, artistic, political and social events? From a methodological viewpoint, this study adopted the analysis-interpretation comparison proposed by the French Discourse Analysis, since that is the field in which this thesis is inserted. In addition, we are supported by valuable concepts by Michael Foucault, such as subject, discourse, discursive formation, among other notions, to provide and disseminate a broad view to support our analyses and stimulate reflections on political, historical, social, and ideological issues regarding the production of meaning in Buarque’s songs. To provide a space dedicated to understanding the author’s figure in this pathway to writing, authorship became a relevant concept, as it reveals important features about the song-statement linked to the goal of this thesis. The results of the analyses indicate that there are regularities regarding the place of the discursive subjects in the songs investigated in the two Brazilian political regimes, especially when this place is related to those who are excluded/oppressed by the social and political spheres. Put into motion by history, these discourses do not cease to appear, and they establish and manifest themselves in defense of these excluded/oppressed subjects, regardless of the political system in force. This also shows that the figure of the author, Chico Buarque, has become an integral aspect of the discourses of questioning and resistance, as something that distinguishes him.